4. THE PREVALENCE OF INSOMNIA AND ASSOCIATED FACTORS IN PREOPERATIVE PATIENTS AT THORACIC SURGERY DEPARTMENT, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: Adequate sleep during the preoperative period is considered an important factor for postoperative recovery. However, indeed, insomnia is frequently observed among preoperative patients. Therefore, this study aimed to determine the prevalence of insomnia and identify associated factors among preoperative patients at the Thoracic Surgery Department, Bach Mai Hospital.Methods: A cross-sectional study was conducted on 151 elective surgical patients from June to September 2024. Insomnia severity was evaluated using the Insomnia Severity Index (ISI).Results: The finding showed that 33.8% of patients had preoperative insomnia (ISI ≥ 8), with 9.3% experiencing moderate insomnia. Univariable logistic regression analysis revealed associations between older age, comorbidities, and vascular pathology with preoperative insomnia. Additionally, disease-related anxiety, pain, light exposure, sound exposure, and suboptimal environmental temperature were the most frequent factors reported by patients who had insomnia.
Keywords: preoperative insomnia; thoracic and vascular surgery; and patient self-reported factors.